The Needs of the Disabled Children Character in the Novel ‘Rahsia Dhia!’ by Zainun Mustapha - Nik Muhamad Affendi, Nik Rafidah (HRMARS, 2024)
This paper was produced to discuss the needs of a disabled child character in the children's novel Rahsia Dhia. This novel won the 2014 Malaysia Premier Literary Prize in the Children and Youth category. The novel is based on the understanding that every human being has wants and needs to achieve in life. Likewise, Persons with Disabilities (OKU). In general, disabled children also have the same wishes as other normal children. Through this paper, the researcher analyzed children's literature, especially children's novels that highlight the wishes of disabled children. In addition, this study used a qualitative method, which was a text analysis. The Hierarchy of Human Needs Theory (Abraham Maslow) would be applied in this study. The results found that disabled children had the same psychological needs as other normal children, namely physiological needs, safety, love, self-esteem, and self-improvement